Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, (9.x-21) : 3 = 2
=>9x-21=6
=>9x=27
=>x=3
b, (x-39)-21=0
=>x-39-21=0
=>x-60=0
=>x=60
c, 231+(312-x)=531
=>231+312-x=531
=>543-x=531
=>x=543-531
=>x=12
d, 53.(9-x)=53
=>9-x=1
=>x=8
a/ \(\frac{\left(9x-21\right)}{3}=2\)
\(\Rightarrow9x-21=2\cdot3=6\)
\(\Rightarrow9x=6+21=27\)
\(\Rightarrow x=\frac{27}{9}=3\)
b/ \(\left(x-39\right)-21=0\)
\(\Rightarrow x-39=0+21=21\)
\(\Rightarrow x=21+39=60\)
c/ \(231+\left(312-x\right)=531\)
\(\Rightarrow312-x=531-231=300\)
\(\Rightarrow x=312-300=12\)
d/ \(53\cdot\left(9-x\right)=53\)
\(\Rightarrow9-x=\frac{53}{53}=1\)
\(\Rightarrow x=9-1=8\)
231+(312-x)=531
<=> 312 - x = 531 - 231
<=> 312 - x = 300
<=> - x = 300 - 312
<=> - x = - 12
<=> x = 12
( x - 29 ) - 11 = 0
x - 29 = 0 + 11
x - 29 = 11
x = 11 + 29
x = 40
231 + ( 312 - x ) = 531
312 - x = 531 - 231
312 - x = 300
x = 312 - 300
x = 12
\(a,\Rightarrow12x-91=101\\ \Rightarrow12x=192\\ \Rightarrow x=16\\ b,\Rightarrow x:23+45=133\\ \Rightarrow x:23=88\\ \Rightarrow x=\dfrac{88}{23}\\ c,\Rightarrow\left(6x-39\right):7=3\\ \Rightarrow6x-39=21\\ \Rightarrow6x=60\\ \Rightarrow x=10\\ d,\Rightarrow3x-24=\dfrac{148}{73}\\ \Rightarrow3x=\dfrac{1900}{73}\\ \Rightarrow x=\dfrac{1900}{219}\\ e,\Rightarrow\left[{}\begin{matrix}x=0\\x=10\end{matrix}\right.\\ f,\Rightarrow\left[{}\begin{matrix}x=-1\\x=2\end{matrix}\right.\\ d,\left(9-x\right)^3=64=4^3\\ \Rightarrow9-x=4\\ \Rightarrow x=5\\ h,\Rightarrow x=27\\ i,\Rightarrow6x=312\cdot12=624\cdot6\\ \Rightarrow x=624\\ j,\Rightarrow\left(19x+104\right):14=25-42=-17\\ \Rightarrow19x+104=-238\\ \Rightarrow19x=-342\\ \Rightarrow x=-18\)
2: \(=\dfrac{-2}{75}+\dfrac{5}{39}=\dfrac{33}{325}\)
3: \(=\dfrac{6}{11}\left(\dfrac{4}{9}+\dfrac{5}{9}\right)=\dfrac{6}{11}\)
4: \(=\dfrac{7}{19}\left(\dfrac{5}{13}+\dfrac{8}{13}-1\right)=-2\cdot\dfrac{7}{19}=-\dfrac{14}{19}\)
5: \(=\dfrac{2}{7}\left(\dfrac{4}{23}-\dfrac{27}{23}+1\right)=0\)
6: \(=\dfrac{3}{8}\left(\dfrac{3}{7}+\dfrac{4}{7}\right)+\dfrac{11}{8}=\dfrac{3}{8}+\dfrac{11}{8}=\dfrac{14}{8}=\dfrac{7}{4}\)
a: \(x-\dfrac{10}{3}=\dfrac{7}{15}\cdot\dfrac{3}{5}\)
=>\(x-\dfrac{10}{3}=\dfrac{21}{75}=\dfrac{7}{25}\)
=>\(x=\dfrac{7}{25}+\dfrac{10}{3}=\dfrac{21+250}{75}=\dfrac{271}{75}\)
b: \(x+\dfrac{3}{22}=\dfrac{27}{121}\cdot\dfrac{9}{11}\)
=>\(x+\dfrac{3}{22}=\dfrac{243}{1331}\)
=>\(x=\dfrac{243}{1331}-\dfrac{3}{22}=\dfrac{123}{2662}\)
c: \(\dfrac{8}{23}\cdot\dfrac{46}{24}-x=\dfrac{1}{3}\)
=>\(\dfrac{8}{24}\cdot\dfrac{46}{23}-x=\dfrac{1}{3}\)
=>\(\dfrac{2}{3}-x=\dfrac{1}{3}\)
=>\(x=\dfrac{2}{3}-\dfrac{1}{3}=\dfrac{1}{3}\)
d: \(1-x=\dfrac{49}{65}\cdot\dfrac{5}{7}\)
=>\(1-x=\dfrac{49}{7}\cdot\dfrac{5}{65}=\dfrac{7}{13}\)
=>\(x=1-\dfrac{7}{13}=\dfrac{6}{13}\)
dài quá làm hộ câu 1-5 thoy
1) x=21-13
x=8
2)x=-55+41
x=-14
3)x=-21+15
x=-6
4)x=3-3
x=0
5) x= -98-37
x=-135
15 ) 57 - ( x - 46 ) = - 13
57 - x + 46 = -13
103 - x = -13
x = 103 + 13
x = 116
16 ) -x - 23 = -38 - 42
- ( x + 23 )=- ( 38 + 42)
x + 23 = 38 + 42
x = 38 + 42 -23
x = 57
17 ) x - ( - 7 ) = -4 – 14
X + 7 = -18
X = -18-7
X = -25
18 ) 18 - x = -8 - ( - 15 )
18 – x = 7
X = 18 – 7
X = 11
19 ) 45 - ( x + 17 ) = - 26
45 – x - 17 = -26
28 – x = -26
X = 28 + 26
X = 54
20 ) 3. ( x + 5 ) - x - 11 = 24
3x +15 –x – 11 = 24
2x + 4 =24
2x = 24 – 4
2x = 20
X = 20 : 2
X = 10
21 ) 14 - ( x - 7 ) = - 8 - ( - 9 )
14 – x + 7 = 1
21 – x = 1
X = 21 – 1
X = 20
22 ) 15 - ( x - 2 ) = - 7 + 8
15 – x + 2 = 1
17 – x = 1
X = 17 – 1
X = 16
6) x + ( - 71 ) = ( - 55 ) + 85
X – 71 = 30
X = 30 + 71
X = 101
7 ) x - ( - 45 ) = - 63 + 27
X +45 = -16
X = -16 -45
X = - 61
\(180-\left(x+23\right)=65\)
\(-\left(x+23\right)=65-180\)
\(-x-23=-115\)
\(-x=-115+23\)
\(-x=-92\)
\(x=92\)
\(231-\left(312-x\right)=531\)
\(312-x=531-231\)
\(312-x=300\)
\(-x=300-312\)
\(-x=-12\)
\(x=12\)
\(\left(55-x\right)+13=60\)
\(55-x=60-13\)
\(55-x=47\)
\(x=8\)
\(\left(x+3\right)-27=39\)
\(x+3=66\)
\(x=63\)
\(\left(x-8\right)-3=7\)
\(x-8=10\)
\(x\) \(=18\)
180-(x +23)=65
x+23=180-65
x+23=115
x=115-23
x=92
231+(312-x)=531
312-x=531-231
312-x=300
x=312-300
x=12
(55-x)+13=60
55-x=60-13
55-x=47
x=55-47
x=8
(x+3)-27=39
x+3=39+27
x+3=66
x=66-3
x=63
(x-8)-3=7
x-8=7+3
x-8=10
x=10+8
x=18